General practitioners' views and experiences of over-the-counter simvastatin in Scotland - Stewart, Derek (Blackwell Science Inc, 2010)
AIMS: The aims of this study were to determine the views and experiences of Scottish GPs towards CVD risk assessment by community pharmacists and the supply and sale of simvastatin. METHODS: A cross sectional postal questionnaire survey of all primary care general practices in Scotland was carried out. The main outcome measure was GPs' awareness of and opinions regarding OTC simvastatin use, experience of OTC simvastatin and opinions regarding community pharmacist involvement in CHD risk assessment. RESULTS: A response rate of 45.7% was obtained. The majority (92.6%, 428) were aware that community pharmacists could sell simvastatin to reduce the risk of a first coronary event in individuals at moderate risk of CHD. However, over half (55.6%, 257) believed that the OTC sale of simvastatin was inappropriate. Just over half were unaware that the pharmacist's CHD risk assessment for the sale of simvastatin did not include lipid (54.8%, n = 253) or blood pressure measurement (53.7%, n = 248) and 56.7% (262) and 57.8% (267) of respondents, respectively, thought these omissions inappropriate. Almost half of the respondents (48.1%, 222) supported community pharmacists supplying simvastatin as supplementary prescribers while fewer (26.6%, 132) were in favour of supply via an independent prescribing arrangement. CONCLUSION: This study confirms that the majority of GPs do not support the supply of OTC simvastatin by the community pharmacist, being particularly concerned by the lack of cholesterol and blood pressure data in the CHD risk assessment prior to sale. Other methods of pharmacy based simvastatin supply including supplementary prescribing merit further evaluation.